European Union programmes for education and vocational training: development and impact - Ertl, H (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2003)
This paper investigates the development and impact of European Union (EU) programmes in education and training. The programmes must be regarded in the wider context of gradual assumption of competencies in the field of education and training by the European Union. Therefore, the introductory section identifies a number of distinct phases of this process. Section two describes the conceptual background of the interpretatin and implementation of EU educational programmes and the ways in which these programmes potentially influence national provisions in education. In particular the increasing importance of the principle of subsidiarity in the EU legislation and policy is emphasized. In section three, the development of programmes as a means of implementing EU policies in the field of education and vocational training is outlined. The evolution of programmes provides valuable insights into the way they influence national educational provisions. The chronology identifies two generations of programmes, each with a number of'waves' of programmes that were initiated as a reaction to wider economic and societal developments of the time. The varying implementation of patterns of the programmes in the different phases are discussed. In section four, the development of the programmes is interpreted in terms of their influence on the overall and current formulation and implementation of EU education policies. It is argued that the programmes contribute to what has been termed the 'voluntary harmonisation' of the education systems of the EU member states. The contribution concludes with an assessment of the impact of Socrates and Leonardo on the convergence of education and training in Europe. Further, the main current problems of the two programmes are outlined and discussed.